Pre-analytical Errors at the Chemical Pathology Laboratory of a Teaching Hospital - Tapper, Marlene A (J Clin Diagn Res, 2017)
INTRODUCTION: The Chemical Pathology Laboratory at the University Hospital of the West Indies (UHWI) processes specimens received from inpatients, the outpatient department and other medical facilities in Jamaica. Specific rejection criteria are used to determine samples unsuitable for analysis. It has been noted that despite efforts to reduce the number of unacceptable samples received in the laboratory, the problem persists. AIM: The study seeks to provide empirical evidence of the inadequacies from which improvements can be formulated. MATERIALS AND METHODS: Errors recorded in the rejection log in the Chemical Pathology laboratory at the University Hospital of the West Indies for the period were assessed. The types and frequency of errors were determined manually. The yearly rejection ratios over a four-year period were evaluated. RESULTS: The most common causes for rejection were unlabelled samples (37%), incorrectly labelled specimens (23%), samples submitted in an inappropriate tube (14%) and incomplete or inaccurately completed requisition forms (14%). The rejection ratio for 2015-2016 was 2.1%. CONCLUSION: The laboratory must initiate programmes directed at improving the preanalytical process in order to ensure patient safety.